Experimental investigation of solidification and remelting over cryocooled sphere using different concentrations of brine solution as phase change material - Kumar M.; Biswal R.; Kumar A. (My University, 2025)
In this investigation, the solidification, phase change, melting and heat transfer phenomenon from the outer surface of the solid sphere (stainless steel) having different dimensions were analyzed. Liquid nitrogen has been used to cool the sphere at a cryogenic temperature up to - 192 ℃, then dipped the sphere inside a phase change material (brine solution NaCl-H2O of different concentration at ambient temperature) and study the solidification and melting phenomenon. The thickness of ice formation at the outer surface of a sphere is measured for different concentration of brine solution. Variation of ice thickness is also measured for different concentration at different time intervals. It is interesting to note that the time duration of solidification of ice and melting is depending upon the concentration of the solution. Melting behavior of ice is discussed for different concentration. © 2019 International Information and Engineering Technology Association. All rights reserved.